Empowering Housewives in the Environment Training for Making Friendly Liquid Soap in Sumbersari Village - Rudhotul Muhtasanah; Gilang Tri Prasojo; Aina Ulfa Azzahwa; Zulfa Ainurrahma; Farhan Noor Ichsan; Puji Retno Lestari; Achmad Zumarul Abidin; Hamdan Husein Batubara (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Training on making dishwashing soap for women or housewives in Sumbersari Village, Ngampel District, Kendal Regency, was chosen to be disseminated because soap is one of the main needs for maintaining good hygiene standards in everyday life, even though soap is not included in basic needs group. This training in making dishwashing soap aims to enable people in Sumbersari Village, Ngampel District, Kendal Regency, to make their own dishwashing soap to meet their daily needs, reduce people's expenses for purchasing soap which is quite expensive, and open up business opportunities as a home industry. if mass produced. This activity was carried out using the ABCD method through five stages, including identifying community strengths, asset mapping, community economic analysis, creating relationships and activity priorities, as well as monitoring and evaluation. The result of this training is to provide practical experience and increase public knowledge regarding environmentally friendly soap making. This is proven by the participants' ability to understand the process of making environmentally friendly liquid soap well and the participants' desire to apply the knowledge gained